Geomagnetic measurements in Latvia - Shuljakova, Ljuba (Geodesy and Cartography, 2012)
The knowledge of the Earth's magnetic field elements and their dynamic fluctuations over the area concerned are important and can be used for many practical purposes in various fields, including Geodesy and Cartography. Earth's magnetic field tends to vary over time. Unlike the field of a bar magnet, Earth's field changes over time because it is really generated by the motion of molten iron alloys in the Earth's outer core. Long-term magnetic field changes are caused mainly by processes in the Earth's interior, particularly the iron-rich core. Short-term changes of the magnetic field are mainly caused by the currents in the ionosphere and magnetosphere generated by Solar activity. The Latvian Geospatial Information Agency (LGIA) has monumented repeat stations and started periodical Earth's magnetic field declination and inclination measurements in Latvia in 2004. The Network of 6 repeat stations is regularly distributed over the territory of Latvia. The repeat stations of Latvia are: Aglona; Ozolaine; Mikeltornis; Velena; Nigrande; Vilkene. In every repeat station the D, I and F values were determined. Declination on territory of Latvia changes from 4° till 8° in the West – East direction. Magnetometer LEMI – 203 together with theodolite 3T2KP and proton magnetometer PMP 5 were used for measurements. Coordinates of the stations were determined by double frequency (L1/L2) GPS receivers. Determined coordinates were used to obtain geographical azimuth. For reduction the data from Toravere (Estonia) observatory were used, where a variometer from the Nurmijarvi Geophysical Observatory is located. Repeat station points are fixed with benchmarks. Benchmarks are non-magnetic. All the data were sent to the British Geological Survey National Geoscience Data Centre.